Attitudes of French populations towards the disclosure of unsolicited findings in medical genetics. (September 2021) - Rosier, Marion; Guedj, Myriam; Calvas, Patrick; Julia, Sophie; Garnier, Christelle; Cambon-Thomsen, Anne; Muñoz Sastre, Maria Teresa
Next-generation sequencing techniques enable unsolicited findings to be detected. This discovery raises ethical questions concerning the return of these findings. Our study aimed to highlight the views of the general public, patients under supervision and health professionals concerning the acceptability of disclosing unsolicited results to patients. In total, 449 participants assessed scenarios, consisted of all combinations of three factors (patient's information and consent, prevention and treatment of the unsolicited disease and doctor's decision). The response profiles were grouped into six clusters. The participants took ethical aspects into account, but health professionals also considered the medical aspects to a greater extent.